2021
DOI: 10.31590/ejosat.1005547
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Volatile Compounds of Chimonanthus Praecox (Wintersweet) Used as an Ornamental Plant in the Parks of Burdur (Gölhisar)

Abstract: In this study, it was aimed to determine the volatile compounds of the flowers of wintersweet (Chimonanthus praecox) belonging to the Calycanthaceae family which is an exotic species and used as an ornamental plant in the parks of Burdur (Gölhisar) in Turkey. Flower specimens were dried at room temperature, followed by determining their volatile compounds by HS-SPME/GC-MS analysis. As a result of the analysis, 33 volatile compounds belonging to the Chimonanthus praecox species were determined, and the first th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Similarly, studies in different regions revealed varying compositions of floral scent compounds. Li et al (2022) identified a substantial number of compounds in Chimonanthus praecox from Yunnan, whereas 48, 86, 72, 15, 31, 31, 71, 65 and 33 compounds were identified in Chimonanthus praecox from Chongqing ( Zhengguo et al, 2008 ), Hubei ( Li, 2015 ), Jiangxi ( Xu et al, 2006 ), Japan ( Azuma, Totota & Asakawa, 2005 ), Henan ( Zheng et al, 1990 ), Shanghai ( Deng, Song & Hu, 2004 ) Zhejiang ( Li et al, 2009 ), Shandong ( Li et al, 2008 ), and Turkey ( Özderin, Tiğli Kaytanlioğlu & Fakir, 2021 ) respectively. These compounds belonged to categories such as alcohols, acids, esters, terpenes, aldehydes, aromatic compounds, and ketones, with alcohols being the most predominant.…”
Section: Chemical Composition Of Flower Fragrancementioning
confidence: 99%
“…Similarly, studies in different regions revealed varying compositions of floral scent compounds. Li et al (2022) identified a substantial number of compounds in Chimonanthus praecox from Yunnan, whereas 48, 86, 72, 15, 31, 31, 71, 65 and 33 compounds were identified in Chimonanthus praecox from Chongqing ( Zhengguo et al, 2008 ), Hubei ( Li, 2015 ), Jiangxi ( Xu et al, 2006 ), Japan ( Azuma, Totota & Asakawa, 2005 ), Henan ( Zheng et al, 1990 ), Shanghai ( Deng, Song & Hu, 2004 ) Zhejiang ( Li et al, 2009 ), Shandong ( Li et al, 2008 ), and Turkey ( Özderin, Tiğli Kaytanlioğlu & Fakir, 2021 ) respectively. These compounds belonged to categories such as alcohols, acids, esters, terpenes, aldehydes, aromatic compounds, and ketones, with alcohols being the most predominant.…”
Section: Chemical Composition Of Flower Fragrancementioning
confidence: 99%